Impacts of Technology, 4IR and Innovation on Job Opportunities in the Manufacturing Sector: South Africa’s Case - Habanabakize, Thomas (Acta Universitatis Danubius. Œconomica, 2024)
The 4IR and other technological improvements are significant in global socio-economic life. However, this improvement is not only with opportunities as it is associated with some disadvantages. The general belief postulates that the Industrial Revolution would impede individuals’ job opportunities. This study assesses the impact of the industrial revolution, innovation and other economic variables on job opportunities. This objective was achieved by applying the Johansen test for Cointegration and other econometric approaches on time series data from 1990 to 2023. Findings revealed the presence of a long-run relationship among variables. The ICT, innovation, investment and education levels were found to have a significant and positive impact on manufacturing employment while labour force growth has an inverse relationship with employment. The study demonstrates the importance of a combination of innovation and technology in creating jobs and enhancing individuals’ life. Therefore, considering the study findings, it is recommended that, to improve employment opportunities in the manufacturing sector, the government and the Department of High Education should revise the studies curriculum to produce skilled and desired employers. Additionally, to benefit from the 4IR, the South African government is required to improve technological infrastructure to increase the number of citizens using use ICT.